Optimalisasi Gaya Asuh Orang Tua terhadap Tumbuh Kembang Anak Usia Dini Era Digital Perspektif Hadis - Aryanti, Savira Dwi (Tihamah: Jurnal Studi Islam, 2024)
Abstract The digital era has made people start to depend on smartphones. Since the Covid-19 pandemic, smartphones have seemed to dominate various aspects of life. No matter how old or young they are, their hands can't be separated from their smartphones. Even small children are smarter than their parents. However, this is quite concerning, excessive use of smartphones without parental supervision can interfere with the development and development of early childhood. This research focuses on how parents care for early childhood in the digital era, how the Prophet's traditions are related to parenting styles and their quality, and how to optimize parenting styles for children from a hadith perspective. The method used in this research is library research, the data obtained from journal articles, textbooks, books, and relevant websites. This research succeeded in finding that in this digital era many parents give smartphones as a diversion so as not to interfere with their work and through hadith, parents can optimize their parenting patterns for children by imitating the parenting of the Prophet Muhammad.